SEA AND COVID-19 VIRUS: (ANALYSIS EFFECT OF THE COVID-19 PANDEMIC ON MARINE ECOSYSTEM IN INDONESIA IN 2020-2021) - Fadila Aulia (Khazanah: Jurnal Mahasiswa, 2021)
Marine ecosystems are one of the most extensive and diverse biological natural resources. Unfortunately, at this time the marine ecosystem is starting to be threatened. According to preliminary calculations from the Coordinating Team for the National Secretariat for Handling Marine Debris, the total waste entering the sea in 2020 is estimated to reach 521,540 tons, of which around 12,785 tons originate from activities at sea. The purpose of this research is to see how the impact of the Covid-19 pandemic on marine ecosystems. Researchers want to see if the Covid-19 pandemic has a positive impact that can be used as a reference for improving a sustainable marine ecosystem. The method that the researcher uses in this research is the literature study method using previous research journals as a reference for data collection. Based on the literature study that has been carried out, the researchers obtained the results that the Covid-19 pandemic had positive and negative impacts on marine ecosystems. The positive impact caused is the reduction in human activities during the Covid 19 pandemic, making marine ecosystems have a high probability of recovering. While the negative impact is the increase in waste production. Because when the Covid-19 pandemic occurred, many people shopped through online applications. However, seeing that the restriction of human activity during the Covid-19 pandemic has a positive impact on marine ecosystems, this policy can be continued. By limiting visitors who come to marine tourism areas. For example, marine tourism is only opened 3 times a week and visitors who are allowed to come cannot be more than 30 people. This is expected to reduce marine pollution caused by human hands. Keywords : Covid-19 pandemic, marine ecosystem, pollution.